ANALYSIS OF FACTORS AFFECTING THE INTEREST OF ACCOUNTING STUDENTS IN TAXATION PROFESSIONS AFTER THE PANDEMIC PERIOD - Juan Carlos Pangestu; Phebyana Margaretha (Jurnal Ekonomi, 2023)
Taxation aspects must be carried out by all taxpayers in all fields, not only finance. The tax profession is needed so that people report their tax obligations according to tax rules and regulations. For a career in taxation, one must meet the criteria and requirements to become a tax professional. Education is also one of the factors needed to become a professional in taxation. However, the process of becoming a professional in taxation requires a lot of time and interest because you have to attend education and pass a professionalism exam. The research aims to determine the influencing factors Affecting The Interest Of Accounting Students In Taxation Professions After The Pandemic Period The results showed that only the variables of perception and study motivation had an influence on students' interest in working in the field of taxation. While other variables such as Tax knowledge and Market Considerations have no influence on students' interest in working in the field of taxation. The results of this study indicate that what can most influence the interest in the profession are the internal factors of the student such as perception and motivation to learn. Suggestions for further research are to add variables or replace variables that are thought to influence student interest in a career in taxation. Future research can also take research samples at universities or educational institutions outside Jakarta or maybe outside the island of Java province